PROJECT BASED LEARNING SEBAGAI MODEL PEMBELAJARAN TEKS ANEKDOT PADA MAHASISWA UNIVERSITAS ROYAL - Sri Rezki Maulina Azmi; Dewi Anggraeni (Smart Education, 2025)
Abstract: Effective learning is very important to implement, especially through a contextual approach that is in line with real life, known as Project Based Learning (PBL). This PBL model can improve students' high-level thinking skills, especially in learning anecdotal texts. Within the Outcome-Based Education (OBE) curriculum framework, Indonesian language learning begins to focus students on producing products in the form of texts at the end of the learning process. As a facilitator in learning, lecturers must have the competence to guide students in producing products. One strategy that can be taken is to accustom students to interact with learning models that require high-level thinking. This study aims to describe the application of learning models based on high-level thinking skills and steps in learning Indonesian, especially in anecdotal text materials. The method used in this study is a descriptive method with a qualitative analysis approach. The explanation of the application of this learning model is done descriptively. Based on the results of the analysis, the application of the Project Based Learning model in Indonesian language learning can be done through several steps, including: (1) problem solving, (2) involving students in designing products that are oriented towards reality, (3) planning long-term activities, (4) lecturers monitoring the problem solving process related to the project, (5) students focus on solving problems that are relevant to the project, and (6) students are required to produce anecdotal texts as learning products, which at the same time accustom them to reaching cognitive level C6, namely creating and evaluating learning experiences. Keywords: project based learning, model, teks anekdot Abstrak: Pembelajaran yang efektif sangat penting diterapkan, terutama melalui pendekatan kontekstual yang selaras dengan kehidupan nyata, yang dikenal sebagai Project Based Learning (PBL) atau pembelajaran berbasis proyek. Model PBL ini dapat meningkatkan kemampuan berpikir tingkat tinggi mahasiswa, khususnya dalam pembelajaran teks anekdot. Dalam kerangka kurikulum Outcome-Based Education (OBE), pembelajaran Bahasa Indonesia mulai memfokuskan peserta didik untuk menghasilkan produk berupa teks di akhir proses belajar. Sebagai fasilitator dalam pembelajaran, dosen harus memiliki kompetensi untuk membimbing mahasiswa dalam menghasilkan produk. Salah satu strategi yang dapat diambil adalah dengan membiasakan mahasiswa berinteraksi dengan model pembelajaran yang menuntut berpikir tingkat tinggi. Penelitian ini bertujuan untuk mendeskripsikan penerapan model pembelajaran yang berbasis pada kemampuan berpikir tingkat tinggi serta langkah-langkah dalam pembelajaran Bahasa Indonesia, khususnya pada materi teks anekdot. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan analisis kualitatif. Penjelasan mengenai penerapan model pembelajaran ini dilakukan dengan cara deskriptif. Berdasarkan hasil analisis, penerapan model Project Based Learning dalam pembelajaran bahasa Indonesia dapat dilakukan melalui beberapa langkah, antara lain: (1) penyelesaian masalah, (2) melibatkan mahasiswa dalam merancang produk yang berorientasi pada realitas, (3) merencanakan aktivitas jangka panjang, (4) dosen memantau proses penyelesaian masalah yang terkait dengan proyek, (5) mahasiswa fokus pada penyelesaian masalah yang relevan dengan proyek, dan (6) mahasiswa diharuskan untuk menghasilkan teks anekdot sebagai produk pembelajaran, yang sekaligus membiasakan mereka mencapai level kognitif C6, yaitu mencipta dan mengevaluasi pengalaman belajar. Kata kunci: project based learning, model, teks anekdot